Influence of secondary aluminum dross (SAD) on compressive strength and water absorption capacity properties of sandcrete block. Issue 1 (1st January 2019) - Nduka, David O.; Joshua, Opeyemi; Ajao, Adekunle M.; Ogunbayo, Babatunde F.; Ogundipe, Kunle E.
Abstract: Secondary aluminum dross (SAD) is a hazardous by-product of the aluminum smelting industry. Among various recycling options of this waste, construction and building materials applications is one of the value-added options to end dumping. The present study, thereby, investigates the influence of SAD on the mechanical and durability properties of sandcrete blocks (SBs). Five partial replacements 0%, 10%, 20%, 30% and 40% of river sand with SAD were experimented at constant water–cement ratio of 0.45. Sixty-three SB samples of size 150 mm × 225 mm × 450 mm were molded and cured at different ages of 7, 14 and 28 days before the hardened blocks were subjected to water absorption and compressive crushing tests. The study results revealed that the water absorption of SAD-blended samples was found to rise with increasing percentage replacement with SAD. Also, the study revealed that beyond 10% replacement with SAD, the investigated properties fall below the required limits as stated in relevant standards. SBs blended with SAD up to 10% of weight of sand could be beneficial for construction economy, healthy living, ecological and sustainable built environment.